The comparative financial and economic performance of protected areas in the Greater Kruger National Park, South Africa: functional diversity and resilience in the socio-economics of a landscape-scale reserve network. Issue 8 (2nd August 2020) - Chidakel, Alexander; Eb, Candice; Child, Brian
Abstract: Economic contributions of park-tourism are rarely documented for individual parks in developing countries or made relevant to management or governance concerns. If economic monitoring is to aid management, economic studies of tourism are a useful starting point but traditionally yield only narrow metrics or are applied only to public parks despite many parks being connected to private or communal reserves. We evaluated a network of private and public reserves – the Greater Kruger National Park (GKNP) – comparing economic contributions of member reserves while also attributing a range of values in financial, social and political domains to different components of the system, thus enabling integration of results with resilience-oriented management frameworks and decision-making processes. We show that the diversity of management units corresponds with a diversity of values that we argue underpins institutional resilience. Although private reserves constitute only 12% of the land area, visitor spending there is responsible for over 60% of employment, tax and GDP contributions. The national park is less commercialized but accounts for almost all domestic visits by maintaining affordable access, performing a vital political and social function. However, weak community and joint-governance undermines resilience and limits the ability of stakeholders to act on economic monitoring data.